Pemodelan Matematika Opsi Saham Karyawan Menggunakan Metode Binomial Enhanced American - Shintya Nafitri Hayuningrum; Rudianto Artiono (Universitas Negeri Surabaya, 2023)
Employee stock options (ESO) are given to employees as a type of stock option that gives the right (without obligation) to employees to buy a portion of the company's shares within a certain period in the future at a price that has been agreed upon when the option is granted. This study aims to determine the mathematical model of Employee Stock Option using the Enhanced American Binomial method. In this research, a mathematical model has been developed that can be used to calculate the price of employee stock options. The contract price affects the calculation of ESO price. If the initial stock price (S0 ) is less than or equal to the strike price (K), the ESO price tends to be lower. However, if the initial stock price (S0 ) is greater than the strike price (K), the ESO price tends to be higher. Thus, employees will still benefit from the difference between ( S0) and (K), while the company is not burdened heavily in terms of issuing ESO. Keywords: Employee Stock Option, Binomial Enhanced American.